2017
DOI: 10.1038/mp.2017.223
|View full text |Cite
|
Sign up to set email alerts
|

Rare susceptibility variants for bipolar disorder suggest a role for G protein-coupled receptors

Abstract: Bipolar disorder (BD) is a prevalent mood disorder that tends to cluster in families. Despite high heritability estimates, few genetic susceptibility factors have been identified over decades of genetic research. One possible interpretation for the shortcomings of previous studies to detect causative genes is that BD is caused by highly penetrant rare variants in many genes. We explored this hypothesis by sequencing the exomes of affected individuals from 40 well-characterized multiplex families. We identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Further, we have only assessed the shared common genetic variants between AD and BIP. Other genetic variations, like rare structural variants, are also shown to increase the risk of AD and BIP (Lord et al, 2014; Cruceanu et al, 2017). Lastly, most participants in the data used in our study are of European ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we have only assessed the shared common genetic variants between AD and BIP. Other genetic variations, like rare structural variants, are also shown to increase the risk of AD and BIP (Lord et al, 2014; Cruceanu et al, 2017). Lastly, most participants in the data used in our study are of European ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the modest effect sizes of the PRS, they explained only a fraction of the phenotypic variance, and rare mutations such as copy number variants [50] or rare single-nucleotide variants likely also play an important role in each of the families. Sequencing studies carried out in multiplex families have suggested rare variants are involved in the aetiology of BD [51][52][53]. To date, however, it has proven difficult to identify replicable causal associations between rare variants and BD susceptibility.…”
Section: ×10 -4mentioning
confidence: 99%
“…The LRBest group showed a later age of onset (median 28y, interquartile range, IQR [21, 36]) compared to NRBest (median 19, IQR [16, 24]; p<0.00001).…”
Section: Resultsmentioning
confidence: 99%